Fourier-domain optical coherence tomography-guided phototherapeutic keratectomy for the treatment of anterior corneal scarring - Yang, Yu-Li (Int J Ophthalmol, 2020)
AIM: To evaluate the safety, visual and anatomic outcomes of fourier-domain optical coherence tomography (FD-OCT)-guided excimer laser phototherapeutic keratectomy (PTK) combined with photorefractive keratectomy (PRK) surgery in treating anterior corneal scarring. METHODS: Clinical data of 23 eyes of 21 patients with anterior corneal scarring underwent FD-OCT-guided PTK and PRK from Dec. 2014 to Jul. 2016 were reviewed. Patients were assessed for preoperative and postoperative uncorrected visual acuity (UCVA), best spectacle-corrected visual acuity (BSCVA), contrast sensitivity (CS), FD-OCT, corneal topography and colour figures of anterior segments. RESULTS: The preoperative corneal pathologic conditions included viral keratitis (7 patients, 7 eyes), band keratopathy (2 patients, 4 eyes), corneal dystrophy (4 patients, 4 eyes), traumatic corneal disease (2 patients, 2 eyes) and corneal chemical injury (6 patients, 6 eyes). Mean follow-up time was 10.65 (range, 3-19)mo. UCVA (in logMAR) improved from a mean of 0.79 (95%CI, 0.28-1.29) preoperatively to a mean of 0.45 (95%CI, 0.29-0.62) postoperatively (P=0.021). BSCVA (in logMAR) improved from 0.57 (95%CI, 0.27-0.88) preoperatively to a mean of 0.28 (95%CI, 0.15-0.41) postoperatively (P=0.001). Corneal topographic indices postoperatively showed significant improvement in corneal cylinder (P=0.009), the surface regularity index (P=0.007) and surface asymmetry index (P=0.00). Postoperative spherical equivalent averaged -0.53 diopters (-1.49 to 0.42). No complications were associated with the treatment. CONCLUSION: FD-OCT-guided PTK combined with PRK is safe and effective for the treatment of anterior corneal scarring by eliminating or reducing corneal opacities.